Analysis of the Effectiveness of Tax Socialization Activities to Increase Compliance with Paying Land and Building Taxes (Case Study of Communities in Medan Labuhan District) - Siti Aisyah; Ratih Anggraini Siregar; Taufiq Risal; Ina Liswanty; Tika Nirmala Sari; Adiharianto (International Journal of Sustainable Applied Sciences, 2023)
This research aims to determine and analyze the effectiveness of the role of tax socialization in increasing community compliance as taxpayers to pay land and building tax in the Medan Labuhan area which consists of six regions, namely Kampung Besar, Martubung, Sei Mati, PekanLabuhan, Tangkahan and Nelayan Indah. The type of research used in the research is a qualitative method with a descriptive approach. Data was obtained through observation, interviews, documentation and then analyzed. In this research, the researcher looks at and describes the condition of the company and then analyzes it so that the results and findings are useful as material for decision making and problem solving in the future. The results of this research indicate that the implementation of land and building tax collection in Medan Labuhan District is in accordance with existing regulations and has a very important role. All planned activities carried out by the Medan Labuhan District Government can be said to be quite good, although there are still things that need to be improved in terms of PBB collection payments. The obstacles and efforts faced by Medan Labuhan District in implementing land and building tax collection are lack of knowledge regarding PBB collection, different economic levels and awareness of taxpayers in making PBB payments.